Relationship between TyG-related index and hearing loss in people over 45 s in China - Chao Wang; Mengdi Shi; Liangzhen Xie; Chenhao Jiang; Yunxin Li; Jingxiao Li; Shulin Li; Yan Li (Frontiers in Public Health)
BackgroundTriglycerides and fasting glycemic index are biomarkers used to assess the risk of insulin resistance and metabolic syndrome. It and its derivatives such as the TyG-BMI index are currently able to reflect the degree of insulin resistance and are closely related to a variety of metabolic diseases. The relationship between the TyG-BMI index and hearing loss remains underexplored, particularly in the context of aging and public health. This study investigates the association of the TyG index, BMI index, and TyG-BMI index with hearing loss, with a focus on their potential implications for the aging population.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS) database were analyzed using R software. We applied multi-factor logistic regression, linear regression, restricted cubic splines, and subgroup analyses to assess the impact of the TyG index, BMI index, and TyG-BMI index on hearing loss across different age groups.ResultsThe TyG index was not significantly associated with hearing loss. However, both the BMI index and the TyG-BMI index exhibited a positive correlation with hearing loss, particularly among older individuals. The results suggest that as the population ages, higher BMI and TyG-BMI indices may increase the risk of hearing impairment.ConclusionWhile the TyG index does not show a significant link to hearing loss, higher BMI and TyG-BMI indices are associated with an increased risk of hearing loss, especially in older adults. These findings highlight the importance of considering aging-related factors in public health initiatives aimed at preventing hearing loss. Further research is needed to elucidate the mechanisms underlying these associations and to develop age-inclusive strategies for addressing hearing impairment in the aging population.